Impact of Helicobacter pylori infection on histological changes in non-erosive reflux disease - Gatopoulou, Anthie (World J Gastroenterol, 2004)
AIM: The evidence for an association between Helicobacter pylori (H pylori) and gastroesophageal reflux disease, either in non- erosive (NERD) or erosive esophagitis (ERD) remains uncertain. The available data on the histological changes in NERD and the effect on H pylori infection on them are elusive. The aim of this study therefore was to prospectively evaluate the histological findings and the impact of H pylori infection on a group of symptomatic patients with NERD. METHODS: Fifty consecutive patients were prospectively evaluated for symptoms compatible with GORD. In all cases, routine endoscopy and lugol directed biopsies were performed and assessed histologically in a blinded manner. RESULTS: The overall prevalence of H pylori infection was 70%. Twenty-nine patients out of 50 (58%) were NERD patients. No statistical significance was observed between the H pylori status and NERD. The remaining 21 (42%) were diagnosed as follows: 13 (26%), 6 (12%), 2(4%) with esophagitis grade A, B and C respectively. A statistically significant correlation was observed between the H pylori+ and esophagitis grade A, as well as between H pylori- and grade B. Biopsies from 2 patients were not included because of insufficient materials. Histologically, a basal zone hyperplasia was found in 47 (97.91%) patients, alterations of glycogen content in 47 (97.91%), papillae elongation in 33 (68.75%), blood vessels dilatation in 35(72.91%), chronic inflammation in 21 (43.75%), infiltration with eosinophils, neutophils and T-lymphocytes in 4 (8.33%), 6 (12.5%) and 39 (81.25%) respectively. No correlation was observed between the H pylori status and the histological parameters studied either in NERD or GERD. CONCLUSION: Histological assessment can not differentiate symptomatic patients with erosive versus non-erosive reflux disease. Moreover, H pylori infection may not act as an important factor in patients with NERD.